Optimizing the Recovery of State Losses through Civil Lawsuits Against Assets Suspected of Being Proceeds of Corruption - Mancur Sinaga; Maidin Gultom; Sahata Manalu; Ica Karina; Maranatha Purba (Jurnal Smart Hukum (JSH), 2027)
Corruption in Indonesia inflicts massive financial losses on the state, yet the recovery of such losses remains suboptimal despite a robust criminal enforcement framework. This study explores the optimization of state loss recovery through civil lawsuits (gugatan perdata) targeting assets suspected to be proceeds of corruption. Employing a qualitative normative-empirical method, the research analyzes statutory provisions, court decisions, and asset recovery data from 2019 to 2023. The findings reveal that while the state attorney’s authority to file civil claims based on unlawful acts (onrechtmatige daad) under Article 1365 of the Civil Code provides a powerful non-conviction based pathway, its utilization is hampered by fragmented regulations, weak inter-agency coordination, and procedural uncertainties in tracing and securing assets. Case studies show that civil lawsuits have achieved significant recoveries, yet the overall recovery rate against total state losses remains below 15%. The discussion proposes an optimization model that includes the harmonization of legal instruments, establishment of a dedicated asset recovery task force, adoption of non-conviction based forfeiture mechanisms consistent with UNCAC, and enhanced international mutual legal assistance. The model integrates pre-litigation asset preservation, reverse burden of proof for illicit enrichment, and the use of digital forensics for asset tracing. The conclusion asserts that maximizing civil litigation for asset recovery not only reimburses the state treasury but also delivers a strong deterrent effect by incapacitating corrupt actors economically, provided that political will and institutional reform are sustained